2010
DOI: 10.1007/s13353-010-0001-5
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose oral immunization with lyophilized tissue of herbicide-resistant lettuce expressing hepatitis B surface antigen for prototype plant-derived vaccine tablet formulation

Abstract: Efficient immunization against hepatitis B virus (HBV) and other pathogens with plant-based oral vaccines requires appropriate plant expressors and the optimization of vaccine compositions and administration protocols. Previous immunization studies were mainly based on a combination of the injection of a small surface antigen of HBV (S-HBsAg) and the feeding with raw tissue containing the antigen, supplemented with an adjuvant, and coming from plants conferring resistance to kanamycin. The objective of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
101
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 49 publications
6
101
2
Order By: Relevance
“…Since the first reported plant-made HB Ag in A. tumefaciens strain LBA4404-transformated tobacco by Mason et al (1992) there has been a huge research on expressing major HBV viral proteins. Recombinant HBsAg has been expressed in lupine and lettuce (Kapusta et al, 1999), carrot suspension cells (Zhao et al, 2002), soybean (Smith et al, 2002), peanut (Chen et al, 2002), tomato (Ma et al, 2002;Carolina and Francisco, 2004;Wang and Li, 2008;Srinivas et al, 2008), cherry tomatillo (Gao et al, 2003;Guan et al, 2010), potato (Shulga et al, 2004), banana (Sunil-Kumar et al, 2005), apple core and leaves and tomato (Lou et al, 2005), NT-1 cells of tobacco (Sunil-Kumar et al, 2007) and lettuce (Kostrzak et al, 2011). Chen et al (2002) reported a high level expression of HBsAg in peanut, obtained by Agrobacterium-mediated transformation, with the yield of 2.42 µg HBsAg/g of fresh weight.…”
Section: Hepatitis Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first reported plant-made HB Ag in A. tumefaciens strain LBA4404-transformated tobacco by Mason et al (1992) there has been a huge research on expressing major HBV viral proteins. Recombinant HBsAg has been expressed in lupine and lettuce (Kapusta et al, 1999), carrot suspension cells (Zhao et al, 2002), soybean (Smith et al, 2002), peanut (Chen et al, 2002), tomato (Ma et al, 2002;Carolina and Francisco, 2004;Wang and Li, 2008;Srinivas et al, 2008), cherry tomatillo (Gao et al, 2003;Guan et al, 2010), potato (Shulga et al, 2004), banana (Sunil-Kumar et al, 2005), apple core and leaves and tomato (Lou et al, 2005), NT-1 cells of tobacco (Sunil-Kumar et al, 2007) and lettuce (Kostrzak et al, 2011). Chen et al (2002) reported a high level expression of HBsAg in peanut, obtained by Agrobacterium-mediated transformation, with the yield of 2.42 µg HBsAg/g of fresh weight.…”
Section: Hepatitis Bmentioning
confidence: 99%
“…Many of HBsAg expression systems are still undergoing the process of development and optimisation and new plant species are being tested as possible expression systems. The most recent experiments include cucumber (Unni and Soniya, 2010), sandalwood embryogenic cell suspension cultures (Shekhawat et al, 2010), maize (Hayden et al, 2012;Hayden et al, 2015;Shah et al, 2015) and lettuce (Pniewski et al, 2011), as well as the most recent progress in using potato as host system (Rukavtsova et al, 2015). Even though the first effective parental hepatitis B vaccine by yeast has been developed more than 20 years ago, the vaccine still isn't accessible, effective or is costprohibitive for a lot of world's population, especially for areas that need it the most.…”
Section: Hepatitis Bmentioning
confidence: 99%
“…The test for HBsAg was done in mice and it was expressed in transgenic potato plant [73]. The production of many small surface antigens for hepatitis B virus (S-HBsAg) is done by Pniewski et al and they were shown in genetically modified glufosinate-resistant lettuce [74]. The mice was immunized with lyophilized plants by use of oral means.…”
Section: Viral 5111 Hepatitis B Virusmentioning
confidence: 99%
“…First expression of HBV surface antigen in plants [4] Human clinical trial of plant-produced HBsAg [16] First production of HBsAg in transgenic banana [17] Use of rTMV-mediated transient expression to produce~300 mg/kg HBsAg [20] Use of rBeYDV-mediated transient expression to produce 800 mg/kg HBc Ag [24] Tabletised lyophilised transgenic lettuce containing HBsAg VLPs is orally immunogenic in mice [19] Hepatitis C virus…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…It is interesting in this regard that despite the concept of "vaccination via banana" having been hyped in the popular press since the 1990s (eg: http://www.theguardian.com/science/2000/sep/08/ gm.infectiousdiseases), it was not until 2005 that HBsAg was first expressed in transgenic banana fruit in India, albeit at relatively low yield [17]. A recent review has proposed a combination of approaches, with parenteral vaccination with purified plant-produced HBsAg followed by oral boosting with less well purified antigen as tablets or capsules [18]: preliminary studies in mice using lyophilised HBsAg VLP-producing transgenic lettuce converted into tablets appear to add weight to the proposal [19].…”
Section: Hepatitis B Virusmentioning
confidence: 99%